An Overview of Agricultural Communications Programs and Curricula - Ann Reisner (Journal of Applied Communications, 1990)
Agricultural communications faculty and administration must periodically reexamine programs and curricula. A survey of 30 universities examined current program structure and curricular requirements in agricultural communications programs.